Efficacy and safety of rituximab in patients with chronic hypersensitivity pneumonitis (cHP): A retrospective, multicentric, observational study. (October 2020) - Ferreira, Marion; Borie, Raphaël; Crestani, Bruno; Rigaud, Pierre; Wemeau, Lidwine; Israel-Biet, Dominique; Leroy, Sylvie; Quétant, Sébastien; Plantier, Laurent; Dalphin, Jean-Charles; Cottin, Vincent; Marchand-Adam, Sylvain; et al.
Abstract: Background: There are chronic forms of hypersensitivity pneumonitis (cHP) that can progress to pulmonary fibrosis. There is no recommended treatment for patients whose respiratory condition continues to deteriorate in spite of antigen avoidance. Whether rituximab may be beneficial to patients with cHP is unknown. The aim of this study was to describe the course of 20 patients with cHP under rituximab therapy. Methods: This retrospective study was conducted from November 2018 to July 2019 in 7 French university hospitals. Forced Vital Capacity (FVC) was measured 6 months before rituximab therapy onset (M − 6), at rituximab onset (M0), and 6 months later (M+6). Results: FVC decreased significantly in the 6 months preceding the introduction of rituximab (65% [44; 112%] at M − 6 versus 59% [39; 102%] at M0; p = 0.0001), but it did not differ significantly from that at 6 months after the introduction of rituximab (61% [38; 99%]). The decline in FVC between M0 and M+6 (−3% [-15; +19%]) was significantly less than between M − 6 and M0 (−8% [-21; 0%]) (p = 0.0002). Between M0 (37% [16; 73%]) and M + 6 (45% [15; 70%]), the median DLCO remained stable (p = 0.12). DLCO improved at M+6 in 5 of the 8 patients (63%) for whom a DLCO value was available at M+6 improved their DLCO. Conclusion: Rituximab seems well tolerated, and may lead to stabilization or improvement of lung function in some patients. Highlights: Response to corticosteroids in chronic hypersensitivity pneumonia is inconstant. Rituximab could be considered as a therapeutic alternative. Rituximab could stabilize or even improve lung function.